Goat milk extracellular vesicles: immuno-modulation effects on porcine monocyte-derived macrophages in vitro - Franzoni, Giulia; Mecocci, Samanta; De Ciucis, Chiara Grazia; Mura, Lorena; Dell’Anno, Filippo; Zinellu, Susanna; Fruscione, Floriana; De Paolis, Livia; Carta, Tania; Anfossi, Antonio G.; Dei Guidici, Silvia; Chiaradia, Elisabetta; et al. (Frontiers in Immunology, 2023)
Extracellular vesicles (EVs) are nanometric-membrane-bound sub-cellular structures, which can be recovered from milk. Milk EVs have drawn increasing interest due to their potential biomedical applications, therefore it is important to investigate their impact on key immune cells, such as macrophages. In this work, the immunomodulatory effects of goat milk EVs on untreated (moMФ) and classically activated (moM1) porcine monocyte-derived macrophages were investigated using flow cytometry, ELISA, and gene expression assays. These particles were efficiently internalized by macrophages and high doses (60 μg protein weight) triggered the upregulation of MHC I and MHC II DR on moMФ, but not on moM1. In moMФ, exposure to low doses (0.6 μg) of mEVs enhanced the gene expression of IL10, EBI3, IFNB, whereas high doses up-regulated several pro-inflammatory cytokines. These nanosized structures slightly modulated cytokine gene expression on moM1. Accordingly, the cytokine (protein) contents in culture supernatants of moMФ was mildly affected by exposure to low doses of mEVs , whereas high doses promoted the increased release of TNF, IL-8, IL-1α, IL-1β, IL-1Ra, IL-6, IL-10, IL-12. The cytokines content in moM1 supernatants was not critically affected. Overall, our data support a clinical application of these molecules: they polarized macrophages toward a M1-like phenotype, but this activation seemed to be controlled, to prevent potentially pathological over-reaction to stressors.